Clustering Data Remunerasi Dosen Untuk Penilaian Kinerja Menggunakan Fuzzy c-Means - Putri Elfa Mas`udia; Farida Arinie; Lis Diana Mustafa (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Remuneration of lecturers is closely related to the performance of lecturers as stated in Tri Dharma Perguruan Tinggi. The Three critera of Tri Dharma are teaching, research and devotion. The remuneration data will be clustered into some clusters to analyze the lecturers group. Each remuneration data consists of seven attributes such as teaching, research, textbook, training, community service, presence and certificate. For case study, the remuneration data of lecturers of telecommunication engineering will be used.Fuzzy c-means is the clustering method that will be implemented on this system.Different with K-Means, in Fuzzy c-means data will be mapped on each cluster with varying degrees of membership from 0-1. Based on the test results, there are 3 clusters formed with the number of lecturers who enter cluster 0 are 4 lecturers, 10 lecturers in cluster 1 , and 14 lecturers in cluster 2. Based on the analysis of the test result data, cluster 0 has a better value than other clusters because it has the highest cluster center point so that the lecturer's performance value included in cluster 0 is also high close to the cluster center point value.